Utilizing telemedicine for delivery of postoperative care following minimally invasive gynecologic surgery: A randomized controlled trial - Steven Radtke; Randle Umeh; Martha Chavez; Zuleika Curiel; Karla Mendez (Wolters Kluwer Medknow Publications, 2021)
Objectives: Determine if patient satisfaction is greater after delivering postoperative care via telemedicine following minimally invasive gynecologic surgery. Materials and Methods: University-based outpatient clinic; Randomized controlled trial (Canadian Task Force classification I). Females between 18 and 60 years of age scheduled to undergo laparoscopic hysterectomy or laparoscopic excision of endometriosis were invited to participate. Eligible patients were randomized to receive postoperative care either through a traditional office visit or via telemedicine. PSQ-18 satisfaction surveys were performed by phone after the visit. Results: Forty-one patients were analyzed out of which 25 were in the office group and 16 in the telemedicine group. Groups were homogenous to age (41.4 vs. 43.3 p. 48), body mass index (31.9 vs. 30.6 P = 0.52), distance in miles from home (12.7 vs. 12.4 P = 0.92), and parity (P = 0.51). PSQ-18 questionnaire was scored and each category was compared between the office and telemedicine groups. When comparing medians (interquartile range), the general satisfaction and time spent with doctor categories were significantly higher in the telemedicine group (4.0 [4.0, 4.5] vs. 4.5 [4.5, 5.0] P = 0.05), (4.0 [4.0, 4.5] vs. 4.5 [4.0, 5.0] P = 0.05). The remainder of the categories analyzed were not different between groups Technical Quality (4.0 [3.8, 4.5] vs. 4.5 [3.9, 5.0] P = 0.13), Interpersonal Manner (4.0 [4.0, 4.5] vs. 4.5 [4.0, 5.0] P = 0.34), Communication (4.5 [4.0, 4.5] vs. 4.5 [4.3, 5.0] P = 0.21), Accessibility and Convenience (4.0 [3.5, 4.5] v 4.0 [3.6, 4.5] P = 0.84). A chart review was performed, examining the first 30 days after surgery. One (4%) patient in the office group went to the ER after postoperative visit, and 0 in the telemedicine group (P = 0.42). Conclusion: Postoperative care via telemedicine after gynecologic surgery results in higher patient satisfaction.